2014
DOI: 10.1111/clr.12394
|View full text |Cite
|
Sign up to set email alerts
|

Clinical study on survival rate of short implants placed in the posterior mandibular region: resonance frequency analysis

Abstract: Survival rate of short implants after 90 days was lower than that of regular implants. However, short implants may be considered a reasonable alternative for rehabilitation of severely resorbed mandibles with reduced height, to avoid performing bone reconstruction before implant placement. Patients need to be aware of the reduced survival rate compared with regular implants before implant placement to avoid disappointments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 50 publications
5
37
0
4
Order By: Relevance
“…36 The previous study suggested that levels of ISQ higher than 60 result in satisfactory implant stability. 16 In the present study, short and conventional implants presented mean ISQ values above 60 in all the periods evaluated. At the time of implant installation (T0), higher ISQ values were obtained for both groups.…”
Section: Graphsupporting
confidence: 52%
See 2 more Smart Citations
“…36 The previous study suggested that levels of ISQ higher than 60 result in satisfactory implant stability. 16 In the present study, short and conventional implants presented mean ISQ values above 60 in all the periods evaluated. At the time of implant installation (T0), higher ISQ values were obtained for both groups.…”
Section: Graphsupporting
confidence: 52%
“…This finding could be attributed to the low bone quality in the posterior area of the mandibular bone in consequence of the deficient irrigation, which favored the conventional implants due to increased implant length. 16 On the contrary, at T2, short implants showed statistical increases in ISQ values, probably because of the locking being limited to the upper mandibular cortical bone, where the bone is denser, 16 decreasing the intensity of the stresses around the bone. 29 This fact suggests that those implants that produce more tension around the bone led to a higher bone remodeling.…”
Section: Graphmentioning
confidence: 99%
See 1 more Smart Citation
“…Areas with severe bone resorption and limitations in bone height and thickness represent a challenge for oral rehabilitation with dental implants 11,14 , especially in the posterior regions of the mandible and maxilla where the mandibular canal and maxillary sinus floor are located 6,15 . Short implants have emerged as a less traumatic and invasive alternative than reconstructive procedures with bone grafts 6,14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…One alternative that has been proposed is the use of short implants that would have the advantage of eliminating additional surgical procedures to increase bone availability following installation of the implants 6,11 . A literature review reports that previous studies have shown that the use of short implants had a high failure rate compared to conventional implants 12 .…”
mentioning
confidence: 99%